MOTIVATION, COMPETENCE AND EMPOWERMENT IN FARMING GROUP PRODUCTIVITY AT UPTD FISHERIES AND LIVESTOCK - Ano Diana (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — To Test the Effect of Motivation, Competence and Empowerment on Productivity of Farmer Groups in UPTD Fisheries and Animal Husbandry. Research method—This study uses a quantitative approach. In this research, there are four variables, namely the motivation variable as the influencing variable, the competence variable as the influencing variable, the empowerment variable as the influencing variable, and the productivity variable as the affected variable. This research is quantitative and linear. The population in this study were farmer groups in the Kadugede Fisheries and Animal Husbandry UPTD area, amounting to 10,175 people. Because there are many, the authors use the sample as part of the population. The author determines the number of samples by using the Slovin formula, which is determined by 99 people. Result— Multiple Regression Analysis with the addition of X1, X2 and X3 by 1 will increase Y by 0.126 and 0.139 and 0.580, meaning that every increase in Motivation, Competence and Empowerment by 1, will increase Productivity by 0.126 and 0.139 and 0.580. The t-count value of the Motivation variable (X1) has a p-value of 0.045 <0.05, meaning that it is significantly distributed, while t-count is 2.027> from 1.984 which means that it is significant. The t-value of the Competence variable (X2) has a p-value of 0.020 <0.05, which means it is significant, while tcount is 2.362> from 1.984 which means it is significant. The results of the t-test showed that the t-value of the Empowerment variable (X3) had a p-value of 0.000 <0.05, meaning significant, while tcount 8.579> from ttable 1.984, meaning significant. ANOVA test or F test obtained Fcount of 44.908 with a significance level of 0.000. . R Square is 0.586, this means that it can explain that 58.6% Productivity is influenced by Motivation, Competence, and Empowerment factors. Conclusion— The magnitude of the positive influence of motivation on productivity is 12.6%. The magnitude of the influence of Competence on Productivity is 13.9%. The magnitude of the influence of Empowerment on Productivity is 58%. The magnitude of the influence of Motivation, Competence, Empowerment on Productivity together is 58.6% while the remaining 41.4% is influenced by other factors.